Bioclimatic Design Strategies for a Public Plaza in Pekanbaru, Indonesia - Laili Dwi Annisa; R. Naila Yannizur; Syifadiza Hanum; Nurrul Helen; Oriana Paramita Dewi (RUSTIC, 2026)
The development of commercial areas in major cities such as Pekanbaru continues to grow rapidly in line with increasing economic activity and the rising demand for multifunctional public spaces. However, most commercial buildings in Indonesia remain focused on visual image-making and modern aesthetics, with limited consideration for energy efficiency and thermal comfort. This design study examines the application of bioclimatic architectural principles to a three-story commercial plaza whose primary functions include a culinary center, coworking space, and retail area. The aim of this design is to create a climate-responsive and energy-efficient building that ensures optimal thermal comfort for its users. The design method employs a bioclimatic approach through analysis of building orientation, spatial layout, facade treatment, and the integration of passive elements such as vegetated balconies, secondary skin, and overhangs. The design results indicate that the façade strategy using a secondary skin effectively reduces direct heat exposure from the west, while the addition of vegetation on balconies and the roof provides natural shading and enhances the building’s visual quality. Furthermore, the spatial orientation based on sun path and wind flow improves the efficiency of natural lighting and ventilation. Overall, this design demonstrates that the integration of passive architectural elements can create sustainable commercial buildings that are adaptive to tropical climatic conditions.